Development and in vitro assessment of bioactive glass/polymer nanostructured composites with silver. (January 2014) - Vulpoi, A; Simon, V; Ylänen, H; Simon, S
Two composites consisting of non-woven poly-96L/4D-lactide copolymer meshes and a bioactive glass containing silver and silver free were obtained in polyvinyl-alcohol solutions by slurry dipping method under slow mechanical stirring. The development of hydroxyapatite type nanocrystals on samples surface in simulated body fluid proved for both composites the tendency for high level of bioactivity. Their antibacterial effect was evaluated against Gram-negative Escherichia coli and Gram-positive Staphylococcus epidermidis . Both composites showed inhibitory effect on bacterial growth, but only the composite with silver containing bioactive glass proved to have bactericidal effect. The AgCl nanocrystals and Ag3 PO4 particles self-assembled on the surface of this composite proved the release of silver ions into simulated body fluid.